Antimicrobial Properties of α-MSH and Related Synthetic Melanocortins. (2006) - Catania, A.; Colombo, G.; Rossi, C.; Carlin, A.; Sordi, A.; Lonati, C.; Turcatti, F.; Leonardi, P.; Grieco, P.; Gatti, S.
Abstract : The natural antimicrobial peptides are ancient host defense effector molecules, present in organisms across the evolutionary spectrum. Several properties of α-melanocyte stimulating hormone (α-MSH) suggested that it could be a natural antimicrobial peptide. α-MSH is a primordial peptide that appeared during the Paleozoic era, long before adaptive immunity developed and, like natural antimicrobial molecules, is produced by barrier epithelia, immunocytes, and within the central nervous system. α-MSH was discovered to have antimicrobial activity against two representative pathogens, Staphylococcus aureus and Candida albicans . The candidacidal influences of α-MSH appeared to be mediated by increases in cell cyclic adenosine monophosphate (cAMP). The cAMP-inducing capacity of α-MSH likely interferes with the yeast's own regulatory mechanisms of this essential signaling pathway. It is remarkable that this mechanism of action in yeast mimics the influences of α-MSH in mammalian cells in which the peptide binds to G-protein-linked melanocortin receptors, activates adenylyl cyclase, and increases cAMP. When considering that most of the natural antimicrobial peptides enhance the local inflammatory reaction, the anti-inflammatory and antipyretic effects of α-MSH confer unique properties to this molecule relative to other natural antimicrobial molecules. Synthetic derivatives, chemically stable and resistant to enzymatic degradation, could form the basis for novel therapies that combine anti-inflammatory and antimicrobial properties.